Responses of the Necrotrophic Fungus Alternaria brassisicola to the Indolic Phytoalexin Brassinin - N’Guyen, Guillaume Quang; Raulo, Roxane; Porquier, Antoine; Iacomi, Beatrice; Pelletier, Sandra; Renou, Jean-Pierre; Bataillé-Simoneau, Nelly; Campion, Claire; Hamon, Bruno; Kwasiborski, Anthony; Colou, Justine; Benamar, Abdelilah; et al. (Frontiers in Plant Science, 2021)
Alternaria brassicicola is the causative agent of black spot disease in Brassicaceae. During host infection, this necrotrophic fungus is exposed to high levels of antimicrobial defence compounds, such as the indolic phytoalexin brassinin. To gain insights into the cellular mechanisms by which this compound exerts its toxicity and investigate the adaptive strategies used by the fungus, we first analyzed fungal transcriptional responses to short-term exposure to brassinin and then used additional functional approaches. This study supports the hypothesis that indolic phytoalexin primarily targets mitochondrial functions in fungal cells. Indeed, we notably observed that phytoalexin treatment of A. brassicicola disrupted the mitochondrial membrane potential and resulted in a significant and rapid decrease in the oxygen consumption rates. Secondary effects, such as ROS production, changes in lipid and endoplasmic reticulum (ER) homeostasis were then found to be induced. Consequently, the fungus has to adapt its metabolism to protect itself against the toxic effects of these molecules, especially via the activation of high osmolarity glycerol (HOG) and cell wall integrity (CWI) signaling pathways and by induction of the unfolded protein response (UPR).